Hubungan Perawatan Keluarga dengan Efikasi Diri Klien DM di Puskesmas Sayung 1 - Marcella Mahattan Nimas; Moch Aspihan; Iskim Luthfa (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Background : When insulin production drops too low, metabolic abnormalities in the pancreas cause hyperglycemia, or high blood sugar. This condition is known as diabetes mellitus (DM). Patients with diabetes mellitus will require care and support from their loved ones because of the disruption in their self-concept caused by the disease. It is our responsibility as nurses who provide care management to educate our patients and their loved ones about self-care actions they can take to control their blood sugar levels. Objectives: to determine demographic information (gender, age, occupation, education level), create a family care catalog for DM patients, create a self-efficacy catalog after family care, and analyze the relationship between family care and self-efficacy for DM patients. Methods: Cross-sectional research concept with total sampling technique, the number of respondents was 50 people with a questionnaire sheet instrument Results: There were 36 female respondents (72%) and 14 male respondents (28%). The age of the majority of respondents was 56-75 years, 31 people (62%). The highest level of respondent education was high school, 22 people (44%). The majority of respondents who are no longer working are 36 people (72%). The average respondent has suffered from DM for more than 5 years is 30 people (60%). Based on the analysis of family care and self-efficacy, 36 people received good and supportive family care, and 32 people also had high self-efficacy. This study shows the results of statistical tests with the chi-square test and obtained a p value of 0.000 or p <0.05 so that Ho is rejected and Ha is accepted. Conclusion: It can be concluded that there is a relationship between family care and self-efficacy of diabetes mellitus clients at Sayung 1 Health Center